Peasant Movements and Agrarian Change: Venezuela and Brazil compared Movimientos Campesinos y Transición Agraria: Venezuela comparada con Brasil - Smith Ajl, Max (2023)
This thesis situates the emergence of the National Peasant Front Ezequiel Zamora (FNCEZ), the most active of the Venezuelan peasant movements, with respect to modern Venezuelan agrarian history, Venezuelan agrarian class structure, and modern Venezuelan political history. Using a framework derived from a medley of Erik Wolf, Sidney Tarrow, Mark Lichbach, James Scott, Thomas Wickham-Crowley, Deborah Bryceson, Farshad Araghi, and Simon Critchley, I argue that failed peasant revolts, ineffective agrarian reforms, and the concentration of the peasantry into the cities set the stage for a state-reliant capitalist farming industry with an increasing percentage of peasants mired in the morass of semi-proletarianization. In turn, the deepening penetration of neo-liberal capitalism in the countryside made the peasantry squirm and writhe under increasingly intolerable impositions.